Menjadi Berkat Bagi Dunia: Reinterpretasi Visi HKBP dari Perspektif Diakonia Untuk Menjadi Jemaat yang Diakonal - Azwar Anas Pasaribu (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This research aims to reinterpret the vision of the Protestant Batak Christian Huria (HKBP) "to be a blessing to the world" from the perspective of diakonia. This research uses a literature method with a qualitative approach through the study of theological literature, history, and church documents. The results of the study show that diakonia is the main entrance to the gospel message in the Land of Batak that brings social, educational, and health transformation to the community. However, in its development, HKBP's diakonic practice tends to be centered on church institutions and has not fully involved the active participation of congregation members. In addition, there is a tendency for service that is charitable without sustainable empowerment. Therefore, it is necessary to reinterpret the vision of HKBP by emphasizing the formation of a diaconal congregation, where all members of the congregation should be equipped and encouraged to be involved in the service of love in the community. Thus, diakonia is not only a program of the church, but a real and transformative practice of living of faith, so that the church truly becomes a blessing to the world. Furthermore, strengthening congregational capacity through contextual theological education and the development of local needs-based ministries is an important strategy in realizing a responsive and inclusive church. This approach is expected to be able to encourage the sustainability of diakonia services which not only has a short-term impact, but also builds independence and community welfare holistically.